The Role of Positive Madrasah Climate in Strengthening Student Character through Values-Based Islamic Education - Yakub, Ali; Shobariyah, Eti; Wasehudin; Sa'ad, Saudi; Nadhirah, Yahdinil Firda (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study investigates the implementation of a positive madrasah climate grounded in Islamic educational values and its role in shaping student character at State Islamic Senior High School (MAN) 1, Cilegon City. Employing a descriptive qualitative approach with a case study design, data were gathered through participatory observation, in-depth interviews with 15 purposively selected informants—comprising the principal, deputy principals, teaching staff, and students—and systematic documentation of institutional records, learning instruments, and habituation program logs. Thematic analysis following Miles et al.'s (2014) interactive model was applied across three stages: data reduction, data presentation, and conclusion drawing. Source triangulation and technique triangulation were performed to ensure data credibility and trustworthiness. The findings reveal three interrelated dimensions of character formation: (1) a spiritual environment actualized through systematic religious habituation, exemplary conduct of educators, and a conducive physical-social atmosphere; (2) values-based learning that integrates the Love-Based Curriculum (KBC) framework—encompassing love for Allāh and the Prophet, love for knowledge, love for the environment, love for self and others, and love for the nation—into every subject's planning, implementation, and evaluation; and (3) a complex ecology of supporting and inhibiting factors that mediate the effectiveness of these two dimensions. The study concludes that character formation in Islamic secondary schools demands an integrated ecosystemic approach rather than ceremonial implementation, and that the deliberate alignment of madrasah climate with values-based learning produces graduates who are academically competent, morally grounded, and spiritually mature. These findings contribute theoretically to Islamic character education discourse and practically to the design of holistic character programs in Indonesian madrasahs.